THE ROLE OF MULTIMODAL LEARNING MATERIALS IN IMPROVING STUDENTS’ VOCABULARY MASTERY IN EFL CLASSROOMS - Treesly Yumiardi Normin Adoe; Vera Rosalina Bulu (SENSEI RESEARCH CENTER, 2023)
Vocabulary mastery is a fundamental component of English language learning because it supports students’ reading comprehension, listening comprehension, speaking fluency, and writing accuracy. However, many students still experience difficulties in understanding, remembering, and using English vocabulary because vocabulary is often taught through memorization, translation, and isolated word lists. This study aims to examine the role of multimodal learning materials in improving students’ vocabulary mastery in English as a foreign language classrooms. The study employed a mixed-method design by combining a quasi-experimental pretest-posttest control group design with qualitative interviews and classroom observations. The participants consisted of 64 seventh-grade students divided into an experimental group and a control group. The experimental group learned vocabulary through multimodal materials integrating text, images, audio, short videos, pronunciation models, and contextual tasks, while the control group received conventional vocabulary instruction. Quantitative data were collected through vocabulary mastery tests and analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, and effect size analysis. Qualitative data were obtained from student interviews, teacher interviews, classroom observations, and learning documents. The findings showed that students in the experimental group achieved significantly higher vocabulary gains than those in the control group. Qualitative findings revealed that multimodal materials supported vocabulary learning through visual anchoring, auditory reinforcement, contextual meaning-making, repeated exposure, and increased engagement. The study concludes that multimodal learning materials can improve students’ vocabulary mastery when they are pedagogically structured and aligned with vocabulary learning objectives.